Assessing prevalence of eating disorders and eating disorder symptoms among lightweight and open weight collegiate rowers - Gapin, J. I.; Kearns, B. (Journal of Clinical Sport Psychology, 2013)
Athletes in sports with weight requirements may be especially vulnerable to eating disorders (EDs), yet there is limited research regarding collegiate rowers. Therefore, the purpose of this study was to examine prevalence rates of ED symptoms in 133 male and female competitive collegiate rowers in lightweight and open weight programs. This is the first study to examine eating pathology in rowers using a diagnostic tool based on DSM-IV criteria, the Q-EDD, and examining ED symptoms using the EDI-2 (drive for thinness [DT] and body dissatisfaction [BD]). The majority of rowers were classified as symptomatic (n = 65; 49%) or clinical (n = 5; 4%). Lightweight rowers had a significantly higher prevalence of eating pathology and a significantly greater DT and BD than open weight rowers. Males had considerably higher prevalence of eating pathology than females, but females had significantly greater BD. Ongoing monitoring of rowers` eating behaviors is highly encouraged. Implications for counseling and prevention are discussed.